2015
DOI: 10.1590/s0004-28032015000400011
|View full text |Cite
|
Sign up to set email alerts
|

BOWEL PREPARATION BEFORE COLONOSCOPY FOR CHILDREN: comparison of efficacy of three different methods

Abstract: -Background -Colonoscopy is an important diagnostic and therapeutic procedure. Adequate bowel preparation is mandatory.Several regimens were discussed in the literature. Among the drugs which has recently used, polyethylene glycol is one of the most popular agents. Objectives -The aim of this study was to compare efficacy of three different methods for 1 day preparation before colonoscopy. Methods -This study included children with the range of ages (2-21) who had an indication of colonoscopy. Exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…PEG-3350 based BP protocols have been very popular in the last 2 decades in children [1]. The efficacy of PEG for BP has been a subject of investigation for a long time, and satisfactory results varied between 70 and 95% in these studies [16,17]. However, the dose and duration of PEG used, the duration of clear liquid diet, and the medications added to PEG differ as well as the scales used to evaluate the efficacy of the BPs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PEG-3350 based BP protocols have been very popular in the last 2 decades in children [1]. The efficacy of PEG for BP has been a subject of investigation for a long time, and satisfactory results varied between 70 and 95% in these studies [16,17]. However, the dose and duration of PEG used, the duration of clear liquid diet, and the medications added to PEG differ as well as the scales used to evaluate the efficacy of the BPs.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of PEG with a stimulant laxative is another bowel cleansing regimen that was tried [5,6,10,16,17]. Two prospective pediatric studies investigated 2-day PEG-3350 combined with bisacodyl cleanout regimen [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PEG is considered an effective intestinal cleansing regimen and is associated with less electrolyte imbalance (23,24). Several studies (14,(25)(26)(27) have demonstrated that PEG is superior or equal on efficacy of bowel preparation comparing with other regimens (senna, NaPico with magnesium citrate, sodium phosphate) among pediatric populations. Both senna and sodium phosphate can cause side effects, such as dehydration, which lead extra fluids intake to the patients.…”
Section: Discussionmentioning
confidence: 99%